MAXIMIZING THE POTENTIAL: EFFECTIVE IMPLEMENTATION OF AI IN BLOCKCHAIN TECHNOLOGY (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2023)
Blockchain technology has emerged as a transformative solution in various industrial sectors, offering services such as smart factories, smart supply chains, and smart solutions. To harness its full potential, it is crucial to integrate quality drivers and enablers that encompass technologies like the Internet of Things (IoT), robotics and artificial intelligence, cybersecurity, 3D printing, cloud databases, augmented and virtual reality, among others. The advent of Industry 4.0 has further highlighted the benefits of blockchain technology, including improved production processes, enhanced product quality, increased customer satisfaction, and precise service delivery. Additionally, the distributed ledger technology underlying blockchain enables the implementation of innovative reward programs and automated voucher management, revolutionizing the way transactions are conducted. By establishing a comprehensive supply system that connects producers to the end consumer, blockchain facilitates accurate inventory management and enables seamless communication between consumers and distributors for inquiries and orders. This paper explores the effective integration of artificial intelligence into blockchain technology, unlocking new possibilities for optimization and efficiency across various industries.